PENYULUHAN KEPADA MASYARAKAT TERKAIT PENYIMPANAN SUPLEMEN DI WILAYAH KELURAHAN DUREN SAWIT - Rahmat Widiyanto; Doni Iswandani; Farida Tuahuns; Muthia Rachma Wulandari (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
The COVID-19 pandemic that occurred several years ago caused changes in lifestyle and supplement consumption patterns by the public. This increase in consumption patterns causes the need for awareness regarding supplement storage so that the quality of supplements is maintained. This Community Service (PkM) activity was carried out for 85 community members in the Duren Sawit Village area. The aim of this PkM activity is to increase public knowledge regarding storing supplements properly and correctly through administering pretest and posttest questionnaires. The success of the PkM program is measured through an increase in the posttest questionnaire score. Keywords: Covid-19, Storing supplements, Questionnaire